2013
DOI: 10.1016/j.jelekin.2013.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Intersession reliability of a posturo-stabilometric test, using a force platform

Abstract: a b s t r a c tAim of the study: To evaluate the intersession reliability of a posturo-stabilometric examination. Methods: Single blind clinical trial conducted in two sessions over two weeks. 44 healthy volunteers free from postural and temporomandibular disorders. All the subjects complied with the criteria for completing the study. All the subjects underwent two sessions of posturo-stabilometric examinations in different visual and mandibular conditions. Sway area, sway length and the coordinates of the cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
18
1
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 26 publications
4
18
1
2
Order By: Relevance
“…Our study also compared the stabilometric parameters among the above mentioned dental conditions. Previous studies assessed the reliability of stabilometric analysis using a force platform and showed good intra-and intersession reliability [25,26]. Path length is considered to be a valid outcome measurement in numerous balance conditions; the smaller the path length, the better is the postural stability [27].…”
Section: Discussionmentioning
confidence: 99%
“…Our study also compared the stabilometric parameters among the above mentioned dental conditions. Previous studies assessed the reliability of stabilometric analysis using a force platform and showed good intra-and intersession reliability [25,26]. Path length is considered to be a valid outcome measurement in numerous balance conditions; the smaller the path length, the better is the postural stability [27].…”
Section: Discussionmentioning
confidence: 99%
“…From a biomechanical point of view the measurement of the centre of pressure (CoP) displacement by means of force platforms is the most employed system to evaluate static upright posture. This methodology of postural assessment proved good intra-session and inter-session reliability, above all referred to sway length, CoP X and CoP Y parameters [ 2 ]. In addition to standard postural sway parameters, Collins and De Luca [ 3 ] introduced the stabilogram diffusion analysis (SDA) demonstrating that in a static upright posture, CoP trajectories could be modelled as a fractional Brownian motion and that two different neuro muscular control mechanisms operated: open-loop control schemes over short term intervals and closed loop control schemes over long-term intervals.…”
Section: Introductionmentioning
confidence: 99%
“…The posturo-stabilometric parameters as well as the postural sway and the velocity showed acceptable reliability (5,8). The repeatability of postural variables, like the sway, was con rmed by Ishizaki et al (9).…”
Section: Introductionmentioning
confidence: 84%